Between Mania and Phobia: Feminism, Science Fiction, and Technoculture in the 1980s. Issue 3 (1st December 2020) - Andrews, Chad
Abstract : The 1980s in the United States are now understood as years of widespread cultural and ideological fracture. Neoliberalism became the nation's economic mantra, détente was jettisoned in favor of military build-up, and conservative backlash movements surfaced to counter the feminist gains of previous decades. These and other developments materialized out of a multitude of conflicts, a crisis of ideas, words, and practices competing to maintain or rework the nation's defining structures. This paper argues that technology played a central role in the decade's discordant years, both materially and ideologically, and that certain works of feminist science fiction—particularly by Lois McMaster Bujold, who is the focus here, but also Sheri S. Tepper, Octavia E. Butler, Joan Slonczewski, and others—imagined new structures and practices embedded within the confines of modern technoculture. By doing so, they avoided a prevailing dichotomy conceptualized by Carol Stabile: either technomania, a headlong, manic rush into all things technological, or technophobia, a retreat from such things into a romanticized and idyllic past. Situated between mania and phobia, these works imagined alternatives to the kind of binary thinking that dominates our political climate, as well as visions of what a radically reformed—but also deeply technological—society could look like.